Macroeconomic Factors, Financing Contracts, and Non-Performing Financing in Islamic Commercial Banking - Ainina, Ananda Nur; Anggraini, Ika Khusnia (Islamic Economics and finance in Focus, 2026)
Maintaining financing quality is a critical challenge for Islamic Commercial Banks amid increasing macroeconomic uncertainty and the growing complexity of financing portfolios. While previous studies have primarily emphasized macroeconomic determinants of Non-Performing Financing (NPF), limited attention has been given to the role of financing contract characteristics in shaping financing risk. This study aims to examine the effects of macroeconomic factors, including inflation, the BI Rate, and the exchange rate, together with murabahah and mudharabah financing contracts on NPF in Islamic Commercial Banks. The study employs a quantitative approach using monthly secondary data from January 2018 to December 2024 obtained from the Financial Services Authority (OJK), Bank Indonesia, and Investing.com. The Autoregressive Distributed Lag (ARDL) model is applied to estimate both short-run and long-run relationships among the variables. The findings reveal that, in the long run, inflation, the BI Rate, the exchange rate, and mudharabah financing do not significantly affect NPF, whereas murabahah financing has a significant negative effect. In the short run, inflation negatively and significantly affects NPF, while the remaining variables show no significant influence. These findings highlight the importance of financing contract composition, particularly murabahah financing, in maintaining financing quality and strengthening risk management strategies to support the stability of the Islamic banking sector.